Interspecific variation in the temperature response of mesophyll conductance is related to leaf anatomy. (5th September 2022) - Huang, Guanjun; Zhang, Qiangqiang; Yang, Yuhan; Shu, Yu; Ren, Xifeng; Peng, Shaobing; Li, Yong
SUMMARY: Although mesophyll conductance ( g m ) is known to be sensitive to temperature ( T ), the mechanisms underlying the temperature response of g m are not fully understood. In particular, it has yet to be established whether interspecific variation in g m – T relationships is associated with mesophyll anatomy and vein traits. In the present study, we measured the short‐term response of g m in eight crop species, and leaf water potential ( Ψ leaf ) in five crop species over a temperature range of 15–35°C. The considered structural parameters are surface areas of mesophyll cells and chloroplasts facing intercellular airspaces per unit leaf area ( S m and S c ), cell wall thickness ( T cw ), and vein length per area (VLA). We detected large interspecific variations in the temperature responses of g m and Ψ leaf . The activation energy for g m ( E a, gm ) was found to be positively correlated with S c, although it showed no correlation with T cw . In contrast, VLA was positively correlated with the slope of the linear model of Ψ leaf – T ( a ), whereas E a, gm was marginally correlated with VLA and a . A two‐component model was subsequently used to model g m – T relationships, and the mechanisms underlying the temperature response of g m are discussed. The data presented here indicate that leaf anatomy is a major determinant of the interspecific variation in g m – T relationships. Significance Statement: The mechanisms underlying the temperature response of g m are not fully understood, the data presented here indicate that leaf anatomy is a major determinant of the interspecific variation in g m – T relationships.